Hijacking Endocytosis and Autophagy in Extracellular Vesicle Communication: Where the Inside Meets the Outside - Pedrioli, Giona; Paganetti, Paolo (Frontiers in Cell and Developmental Biology, 2021)
Extracellular vesicles, phospholipid bilayer-membrane vesicles of cellular origin, are emerging as nanocarriers of biological information between cells. Extracellular vesicles transport virtually all biologically active macromolecules (e.g. nucleotides, lipids, and proteins), thus eliciting phenotypic changes in recipient cells. However, we only partially understand the cellular mechanisms driving the encounter of a soluble ligand transported in the lumen of extracellular vesicles with its cytosolic receptor. A step required to evoke a biologically relevant response. In this context, we review herein current evidence supporting the role of two well-described cellular transport pathways: the endocytic pathway as the main entry route for extracellular vesicles and the autophagic pathway driving lysosomal degradation of cytosolic proteins. The interplay between these pathways may result in the target engagement between an extracellular vesicle cargo protein and its cytosolic target within the acidic compartments of the cell. This mechanism of cell-to-cell communication may well own possible implications in the pathogenesis of neurodegenerative disorders.